Associative and non-associative plasticity in Kenyon cells of the honeybee mushroom body - Szyszka, Paul; Galkin, Alexander; Menzel, Randolf (Frontiers in Systems Neuroscience, 2008)
The insect mushroom bodies are higher-order brain centers and critical for odor learning. We investigated experience dependent plasticity of their intrinsic neurons, the Kenyon cells. Using calcium imaging, we recorded Kenyon cell responses and investigated non-associative plasticity by applying repeated odor stimuli. Associative plasticity was examined by performing appetitive odor learning experiments. Olfactory, gustatory and tactile antennal stimuli evoked phasic calcium transients in sparse ensembles of responding Kenyon cells. Repeated stimulation with an odor led to a decrease in Kenyon cells’ response strength. The pairing of an odor (CS) with a sucrose reward (US) induced a prolongation of Kenyon cell responses. After conditioning, Kenyon cell responses to a rewarded odor (CS+) recovered from repetition-induced decrease, while the responses to a non-rewarded odor (CS-) decreased further. The spatio-temporal pattern of activated Kenyon cells changed for both odors when compared with the response before conditioning but the change was stronger for the CS-. These results demonstrate that Kenyon cell responses are subject to non-associative plasticity during odor repetition and undergo associative plasticity after appetitive odor learning.